Proarrhythmic atrial calcium cycling in the diseased heart - Voigt, Niels; Nattel, Stanley; Dobrev, Dobromir (Calcium signaling, 2012)
During the last decades Ca2+ has been found to play a crucial role in cardiac arrhythmias associated with heart failure and a number of congenital arrhythmia syndromes. Recent studies demonstrated that altered atrial Ca2+ cycling may promote the initiation and maintenance of atrial fibrillation, the most common clinical arrhythmia that contributes significantly to population morbidity and mortality. This article describes physiological Ca2+ cycling mechanisms in atrial cardiomyocytes and relates them to fundamental cellular proarrhythmic mechanisms involving Ca2+ signaling abnormalities in the atrium during atrial fibrillation.